Ultrafine Grinding Process Calculation of Meat-Bone by-Product - Kakimov, Aitbek; Bekeshova, Gulvira; Akimov, Mukhamedzhan; Bakiyeva, Anar; Kadyrbayev, Yerlan; Zalilov, Rustem; Baykin, Yuriy; Cherkasova, Elmira; Imangaliyeva, Zhadyra (International Journal of Engineering and Technology, 2018)
This paper presents the method of calculating the cutting process of meat-bone by-products using rotary grinders. The cutting process is performed by cutting wheels and is counted according to the calculation of the cutting force, speed of cutting wheels, gap between the wheels and stress of the materials.Â